Investigation of sex-specific effects of apolipoprotein E on severity of EAE and MS. Issue 1 (December 2015) - Schrewe, L.; Lill, C. M.; Liu, T.; Salmen, A.; Gerdes, L. A.; Guillot-Noel, L.; Akkad, D. A.; Blaschke, P.; Graetz, C.; Hoffjan, S.; Kroner, A.; Demir, S.; et al.
Abstract Background Despite pleiotropic immunomodulatory effects of apolipoprotein E (apoE)in vitro, its effects on the clinical course of experimental autoimmune encephalomyelitis (EAE) and multiple sclerosis (MS) are still controversial. As sex hormones modify immunomodulatory apoE functions, they may explain contentious findings. This study aimed to investigate sex-specific effects ofapoE on disease course of EAE and MS. Methods MOG35-55 induced EAE in female and maleapoE -deficient mice was assessed clinically and histopathologically.apoE expression was investigated by qPCR. The association of the MS severity score (MSSS) andAPOE rs429358 and rs7412 was assessed across 3237 MS patients using linear regression analyses. Results EAE disease course was slightly attenuated in maleapoE -deficient (apoE −/− ) mice compared to wildtype mice (cumulative median score:apoE −/− = 2 [IQR 0.0–4.5]; wildtype = 4 [IQR 1.0–5.0];n = 10 each group, p = 0.0002). In contrast, EAE was more severe in femaleapoE −/− mice compared to wildtype mice (cumulative median score:apoE −/− = 3 [IQR 2.0–4.5]; wildtype = 3 [IQR 0.0–4.0];n = 10, p = 0.003). In wildtype animals, apoE expression during the chronic EAE phase was increased in both females and males (in comparison to naïve animals;p < 0.001). However, in MS, we did not observe a significant association between MSSS and rs429358 or rs7412, neither in the overall analyses nor upon stratification for sex. Conclusions apoE exerts moderate sex-specific effects on EAE severity. However, the results in theapoE knock-out model are not comparable to effects of polymorphic variants in the humanAPOE gene, thus pinpointing the challenge of translating findings from the EAE model to the human disease.